The Resurgence of Central Asia - M. Ehsan Ahrari (International Institute of Islamic Thought, 1996)
As Boris Yeltsin's ruthless suppression of Chechnya's struggle for independence becomes one more item in a series of turbulent and bloody events involving Russia and some of the republics of the former Soviet union and the former Yugoslavia, Ahmad Rashid's The Resurgence of Central Asia: Islam or Nationalism grows in significance for students of that region. The author is a Pakistani journalist with a vast knowledge of the area. He has utilized effectively his many travels to the region in developing an authoritative history of Central Asia. Rashid shifts gears back and forth in history quite effectively in this study to make his points. For instance, in the first chapter he notes that "much of the world's ancient history originated in Central Asia, for it was the birthplace of the great warrior tribes that conquered Russia, India, and China" (p. 8). Also note his following observation: "Central Asia has always been different At the heart of Central Asia is not the story of princes and their courts, but the story of the nomad and his horse" (p. 9). In the same chapter, he quotes a Turkoman foreign ministry official's concern, expressed to him in the aftermath of the Soviet Union's implosion to the effect that "the future is extremely bleak. The West will help Russia and other Slav republics to survive, but who will help us?" (p. 4). This book is replete with such examples. The first chapter contains a condensed version of the " great game" between the two colonial powers of the eighteenth and nineteenth centuries: Russia and Britain. Russia underwent two major revolutions in the twentieth century: one in 1917 and the second in 1991. The first revolution, bloody as it was, ...